World Class Manufacturing Principle(S): A Study on Low Value High Volume Goods (FMCG) (Global Journal of Management and Business Research, 2018)
Abstract not found
Keywords: effective value-addition; fast moving consumer goods; ISO 9001; world class manufacturing units